GPS Navigation System on Autonomous Ship as An Effort to Increase Fish Catch for Fisherman in Pamekasan Indonesia - Bambang Sampurno; Ilham Farhansyah Putra; Mashuri; Eddy Widiyono; Mahirul Mursid; Suhariyanto (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
Currently most of the marine fishing in Indonesia uses traditional boats with navigation systems using compasses and mobile phones. Besides being ineffective, this fishing system also has a high risk, so a safer fishing system is needed, namely using an autonomous boat with a system capable of attracting fish. The use of the Autonomous Surface Vehicle (ASV) for monitoring and fishing purposes has been carried out by Aryusmal (2018) [1] , namely using GPS equipped with an Arduino Uno microcontroller to carry out ship movements, and an error of 1.5 m was obtained. Whereas Permana (2018) [2] made an ASV ship with GPS equipped with an APM microcontroller and Arduino Uno, an error of 30 cm was obtained. Referring to the need for a safe fish system and the results of previous research, this paper designed an autonomous ship with a GPS navigation system using a pixhawk microcontroller which is supported by the use of a brushless motor as the main propulsion of the ship and mission planner software to determine navigation waypoints. This system is able to monitor in real time and save the results of navigation and compass movements up to the last waypoint on the Pixhawk microcontroller. To find out the performance of the ASV, waypoint latitude and longitude tests were carried out on a laboratory and field scale. Laboratory test results have an error of 1.7%, while the results of field testing error errors that occur are 4.4% at longitude and the smallest error is 1.3% at latitude. This error occurred due to field conditions due to sea water shocks. However, this error did not really affect the movement of the ASV ship, because the shift was not too far.